2011
DOI: 10.1097/mcg.0b013e3181e5d1c5
|View full text |Cite
|
Sign up to set email alerts
|

Patients With IBD are Exposed to High Levels of Ionizing Radiation Through CT Scan Diagnostic Imaging

Abstract: Patients with IBD, and especially CD patients, undergo frequent diagnostic imaging and thus significant exposure to ionizing radiation. This radiation exposure reaches high levels in 7% of CD patients, mainly from CT scanning. Efforts should be made to minimize the radiation exposure from diagnostic imaging by reducing either the number of studies or radiation dose in modalities with ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 17 publications
1
66
1
1
Order By: Relevance
“…It seems to be a very powerful technique which can be performed quickly in most radiological departments, even though some concerns have been raised regarding radiation exposure [15,16]. In this respect, correlating CD clinical activity with the CTE findings could help to select patients to be referred for CTE, reducing unnecessary radiation exposure [9].…”
Section: Introductionmentioning
confidence: 99%
“…It seems to be a very powerful technique which can be performed quickly in most radiological departments, even though some concerns have been raised regarding radiation exposure [15,16]. In this respect, correlating CD clinical activity with the CTE findings could help to select patients to be referred for CTE, reducing unnecessary radiation exposure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Stein et al 2 reported a mean total CED after 3 years of 12.3 mSv for 1711 patients with hydrocephalus, 21.7 mSv for 3220 patients with pulmonary thromboembolic disease, 18.7 mSv for 5855 patients with renal colic, and 14 mSv for 11,072 patients with cardiac disease. Kroecker et al 25 reported a mean total CED of 14.3 mSv after 5 years for 371 patients with a diagnosis of Crohn's disease. Chen et al 26 reported a mean total CED over 3 years of 23.1 mSv for 90,121 patients who underwent more than one cardiac imaging procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 13.3 % of IBD patients had high CED (defined as the commonly accepted cutoff value of [50 mSV), with CD patients exhibiting the previously reported increased odds of high-dose radiation exposure compared to those with UC [2][3][4]. Other risk factors for increased odds of high-dose radiation exposure uncovered using univariate analyses included the use of IBD therapeutic medications with the exception of mesalamine, prior bowel resection, increased follow-up duration, and a history of perianal disease in CD patients.…”
mentioning
confidence: 99%
“…Given a 20-fold rise in the amount of CT imaging between 1980 and 2000, it is not surprising that an estimated three-quarters of the radiation to which IBD patients are exposed is due to CT scanning [1,2], mostly from abdomino-pelvic examinations, which have largely supplanted conventional contrast enterography in IBD patients. As an example, an 840 % increase in CT enterography use was reported between 2002 and 2007 [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation